2022
DOI: 10.3390/s22072718
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Presence of Intrusive Drilling in Secure Transport Containers Using Non-Contact Millimeter-Wave Radar

Abstract: We employ a 77–81 GHz frequency-modulated continuous-wave (FMCW) millimeter-wave radar to sense anomalous vibrations during vehicle transport at highway speeds for the first time. Secure metallic containers can be breached during transport by means of drilling into their sidewalls but detecting a drilling signature is difficult because the large vibrations of transport drown out the small vibrations of drilling. For the first time, we demonstrate that it is possible to use a non-contact millimeter-wave radar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…With millimeter-wave radar, this study demonstrated the potential of non-contact health monitoring, 8 VOLUME XX, 2017 providing a convenient and interference-free means of monitoring elderly people or patients who require continuous monitoring. Wagner et al [11] explored how non-contact millimeter-wave radar can be used to detect intrusive drilling in secure transportation containers. This technology is expected to be widely used in the security field to ensure the integrity of transportation containers and reduce potential threats.…”
Section: Introductionmentioning
confidence: 99%
“…With millimeter-wave radar, this study demonstrated the potential of non-contact health monitoring, 8 VOLUME XX, 2017 providing a convenient and interference-free means of monitoring elderly people or patients who require continuous monitoring. Wagner et al [11] explored how non-contact millimeter-wave radar can be used to detect intrusive drilling in secure transportation containers. This technology is expected to be widely used in the security field to ensure the integrity of transportation containers and reduce potential threats.…”
Section: Introductionmentioning
confidence: 99%
“…While this work and Refs. [ 23 , 24 ] share the same methodology of extracting the target displacement by unwrapping the phase over the chirp time, Ref. [ 23 ] utilizes the extracted displacement waveform to detect the micron-level vibrations of reflective objects through a lossy material.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Ref. [ 24 ] utilizes the extracted displacement waveform to sense anomalous drilling vibrations during vehicle transport on metallic containers. However, this work filters the extracted displacement waveform to detect the heart sound frequencies and generate time-frequency representations that can be further processed using image classification deep networks.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue of MDPI Sensors is intended to bring together some recent publications related to the application of millimeter and/or terahertz technology to specific application-related implementations in various fields. It covers a number of particular application examples employing terahertz radiation [7][8][9][10][11][12], presents methodological approaches for measurements techniques and concepts [13][14][15][16][17][18][19], as well as some contributions dedicated to recent achievements from the technology side of source and detector development [20][21][22].…”
mentioning
confidence: 99%
“…A nice example showing how various conventional radar and signal processing techniques can be exploited in the millimeter and terahertz regime, as the respective technical system components become available, is presented by Wagner et al [7]. In their contribution, the authors demonstrate the use of a millimeter wave frequency-modulated continuous wave (FMCW) radar for the detection of drilling intrusion in sensitive transport containers.…”
mentioning
confidence: 99%